2007
DOI: 10.1152/ajplung.00311.2006
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α induces MMP-9 expression via activation of Src/EGFR, PDGFR/PI3K/Akt cascade and promotion of NF-κB/p300 binding in human tracheal smooth muscle cells

Abstract: TNF-alpha has been shown to induce matrix metalloproteinase-9 (MMP-9) expression, which, in turn, degrades extracellular matrix in the inflammatory responses. However, the inductive mechanisms of the MMP-9 by TNF-alpha remain unclear. In human tracheal smooth muscle cells, TNF-alpha induced MMP-9 expression and Akt phosphorylation in a time-dependent manner, which was attenuated by the inhibitors of Src (PP1), epidermal growth factor receptor (AG1478), PDGFR (AG1296), and PI3K (LY294002), respectively, reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
150
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 154 publications
(167 citation statements)
references
References 47 publications
15
150
0
2
Order By: Relevance
“…It has been reported that use of acidand neutralized-sphingomyelinase could lead to significant activation of NF B [33][34] , which is consistent with our findings. Many specific inhibitors of the NF B signaling pathway have been used, such as Bay11-7085, SCH66336, PDTC, and lactacystin in the treatment of cancer patients with apoptosis [35][36][37][38] .…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that use of acidand neutralized-sphingomyelinase could lead to significant activation of NF B [33][34] , which is consistent with our findings. Many specific inhibitors of the NF B signaling pathway have been used, such as Bay11-7085, SCH66336, PDTC, and lactacystin in the treatment of cancer patients with apoptosis [35][36][37][38] .…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that the effect of high EGFR in oligodendrogliomas depends greatly on tumor grade, questioning whether there are any differences in expression profiles between the two grades that might account for this. For example, Akt activation can trigger matrix metalloproteinase expression in a p300-dependent mechanism, 28 yet p300 expression is lower in grade III versus grade II oligodendrogliomas. 29 Alternatively, excessive oncogene signaling can sometimes inhibit tumor growth via induction of compensatory antiproliferative mechanisms, such as cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is also a target of cross talk by other signaling cascades, such as G protein-coupled receptors (9) and receptors for bacterial LPS (36). Furthermore, signaling through TNF/TNFRs stimulates EGFR phosphorylation (33,63), resulting in cellular proliferation (3), migration (72), and survival (76).…”
mentioning
confidence: 99%